Studies towards unveiling the association of Gla-rich protein with osteoarthritis - Cavaco, Sofia Isabel Franco (2016)
Osteoarthritis (OA) is a whole-joint disease believed to onset after articular cartilage damage and accompanied by tissue inflammation, abnormal bone formation and extracellular matrix (ECM) mineralization. Gla-rich protein (GRP), the latest discovered vitamin Kdependent protein (VKDP), was shown to accumulate in mouse and sturgeon cartilage, and sites of skin and vascular calcification in human. Therefore, we investigated the possible involvement of GRP with OA development. An osteoarthritic and control samples human biobank was collected and used for the comparative analysis of GRP patterning at transcriptional and translational levels. Two novel GRP alternative spliced transcripts were unveiled in human (GRP-F5 and F6), yet GRP-F1, corresponding to the full-length protein, was shown to be the predominant variant in articular tissues and upregulated in osteoarthritic cartilage. Undercarboxylated GRP was the prevalent protein form found associated with osteoarthritic cartilage and synovial membrane tissues, highly accumulated at sites of calcification, indicating that the impairment of VKDPs -carboxylation may be related with OA. Using a chondrocyte and synoviocyte cell system developed within this project, we further investigated the association of GRP with OA mineralization and inflammatory processes. Upregulation of GRP was found during induced mineralization and inflammation, and associated to cell differentiation towards ECM mineralization and inflammatory responses, in both cellular types. Moreover, the role of GRP was highlighted through functional assays, showing the inhibition of ECM mineralization and decreased inflammatory response following GRP supplementation. While -carboxylation was required for GRP antimineralization function, its anti-inflammatory effect was independent of protein - carboxylation status. Ultimately, using serum samples from our biobank and a comparative proteomic approach, candidate OA biomarkers were identified. Overall, our results demonstrated, for the first time, the involvement of GRP in two of the main pathological processes occurring in OA, contributing for new knowledge regarding disease progression.